Iron tailing concrete and preparation method thereof

By using mixed sand of iron tailings sand, hydrophobic modified iron tailings powder and river sand in concrete, combined with the use of modified glass fibers, the problem of low iron tailings recycling rate is solved, the strength and crack resistance of concrete are improved, and environmental risks are reduced.

CN119797847APending Publication Date: 2025-04-11JIANGSU VOCATION & TECHNICAL COLLEGE OF FINANCE & ECONOMICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510021402.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The low recycling rate of iron tailings is caused by the accumulation of large amounts of land, polluting the environment, and posing safety hazards such as dust, liquidity and collapse.

Method used

Iron tailings sand, hydrophobically modified iron tailings powder and river sand are used to form mixed sand. The concrete strength is improved through "pinning" and "biting" effects, and the impact of iron tailings powder on concrete fluidity is reduced through hydrophobic modification treatment, and the crack resistance is improved by using modified glass fibers.

Benefits of technology

While not affecting the concrete fluidity, the strength and crack resistance of concrete are improved, effectively solving the problem of low iron tailings recycling rate and reducing environmental protection risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231490280000131
    Figure BDA0005231490280000131
  • Figure BDA0005231490280000141
    Figure BDA0005231490280000141
  • Figure BDA0005231490280000151
    Figure BDA0005231490280000151
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses iron tailing concrete and a preparation method thereof.The iron tailing concrete is prepared from, by weight, 160-180 parts of cement, 70-80 parts of slag powder, 70-80 parts of fly ash, 630-740 parts of river sand, 90-140 parts of iron tailing sand, 90-130 parts of hydrophobic modified iron tailing powder, 200-220 parts of fine stone, 790-820 parts of gravel, 140-165 parts of water and 6-10 parts of a water reducing agent; 70 to 90 parts of modified glass fiber; the hydrophobically modified iron tailing powder is obtained by modifying iron tailing powder with a silane coupling agent KH550 and a formaldehyde aqueous solution, and the fineness modulus of the hydrophobically modified iron tailing powder is 0.5-1.5; the modified glass fibers are obtained by modifying glass fibers with a phenol-chlorobutane solution and calcium oxide. The iron tailing concrete effectively solves the problem of low iron tailing recycling rate in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of building materials, and in particular relates to an iron tailings concrete and a preparation method thereof. Background Art

[0002] Iron tailings are waste after ore dressing and are the main component of industrial solid waste. According to incomplete statistics, the tailings and waste rock discharged worldwide are more than 10 billion tons each year. The amount of tailings stored in my country is nearly 5 billion tons, and the annual tailings discharge is as high as more than 500 million tons, of which the annual tailings discharge from ferrous metallurgical mines reaches 150 million tons. However, the comprehensive utilization rate of tailings is only 7%, and the amount of iron tailings stored is as high as more than 10 billion tons, accounting for nearly 1 / 3 of the total tailings storage.

[0003] And due to technical limitations, most iron tailings are disposed of in piles, which not only occupies a large amount of land but also destroys agricultural and forest land. Iron tailings contain extremely fine tailings dust, which is easily generated in windy weather. In addition, iron tailings are easy to flow and leak when stored, which can easily cause collapse and landslides in the rainy season, resulting in accidents.

[0004] Therefore, the comprehensive recycling and utilization of iron tailings has received widespread attention from the whole society. If these iron tailings can be utilized reasonably, it can solve the problem of iron tailings storage to a certain extent, turn waste into treasure, and create economic benefits. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present application is to provide an iron tailings concrete and a preparation method thereof to solve the problem of low iron tailings recovery rate.

[0006] In order to achieve the above objectives, in the first aspect, the present application provides an iron tailings concrete, which is implemented by the following technical solutions:

[0007] An iron tailings concrete comprises the following raw materials in parts by weight:

[0008] 160-180 parts of cement, 70-80 parts of slag powder, 70-80 parts of fly ash, 630-740 parts of river sand, 90-140 parts of iron tailings sand, 90-130 parts of hydrophobic modified iron tailings powder, 200-220 parts of fine stone, 790-820 parts of crushed stone, 140-165 parts of water, 6-10 parts of water reducer, 70-90 parts of modified glass fiber;

[0009] The hydrophobically modified iron tailings powder is obtained by modifying the iron tailings powder with a silane coupling agent KH550 and a formaldehyde aqueous solution, and the hydrophobically modified iron tailings powder has a fineness modulus of 0.5-1.5;

[0010] The modified glass fiber is obtained by modifying the glass fiber with a phenol-chlorobutane solution and calcium oxide.

[0011] By adopting the above technical scheme, the present application adopts iron tailings sand, hydrophobically modified iron tailings powder and river sand to form a mixed sand. Since the surface of the iron tailings sand and hydrophobically modified iron tailings powder particles are rough and the edges and corners are clear and sharp, after the concrete is solidified, the "pinning" and "biting" effects between the iron tailings sand particles, between the hydrophobically modified iron tailings powder particles, between the iron tailings sand particles and other solid particles in the concrete, and between the hydrophobically modified iron tailings powder particles and other solid particles in the concrete can improve the strength of the concrete.

[0012] However, because the surface of iron tailings sand particles is sharp, the friction between solid particles in the concrete system increases. The combination of hydrophobic modified iron tailings powder, iron tailings sand and river sand with smooth and round particle surfaces reduces the friction between particles in the concrete system and reduces the impact of iron tailings sand on the fluidity of concrete. By controlling the amount of iron tailings sand to between 20-30% of the total weight of the mixed sand, the content of particles with rough surfaces can be controlled to reduce the friction between rough iron tailings sand particles and between iron tailings sand particles and river sand particles, thereby reducing the impact of iron tailings sand on the fluidity of concrete.

[0013] In the present application, the sand ratio is controlled within an appropriate range by controlling the ratio of river sand, fine stone and crushed stone. The appropriate sand ratio allows the concrete to meet the strength requirements while improving the fluidity of the concrete. In the present application, iron tailings sand, river sand, fine stone and crushed stone of different particle sizes are used to form a good gradation between each other, so that the concrete obtains excellent density, thereby improving the strength of the concrete.

[0014] Iron tailings powder has a large specific surface area and strong water absorption capacity, which will have an adverse effect on the fluidity of concrete. In this application, the hydrophobically modified iron tailings powder surface after modification has a hydrophobic film, which reduces the impact of the iron tailings powder on the fluidity of concrete; and the hydrophobic film plays a lubricating role for the movement of the hydrophobically modified iron tailings powder particles, further improving the fluidity of the concrete. In addition, the modified glass fiber obtained by hydrophobic modification of phenol-chlorobutane solution can be better dispersed in the concrete system, effectively improving the crack resistance of the concrete.

[0015] More importantly, under the waste heat of concrete hydration, formaldehyde in the hydrophobic modified iron tailings powder can be evaporated, and the formaldehyde, silane coupling agent and phenol in the hydrophobic modified iron tailings powder and modified glass fiber can be cross-linked in the concrete system to form a "reinforcement body" in which a number of hydrophobic modified iron tailings powders are connected around the modified glass fiber; the "reinforcement body" has a linear modified glass fiber as the main frame and a number of granular hydrophobic modified iron tailings powders as "claws" to form a structure similar to a mace, so that the special structural characteristics of the "reinforcement body" enable it to have a "pinning" and "biting" effect with other solid particles in the concrete system, further improving the strength of the concrete; not only that, the micro-network structure formed by cross-linking of formaldehyde, silane coupling agent and phenol between the hydrophobic modified iron tailings powder and the modified glass fiber can further improve the mechanical properties of the concrete.

[0016] In addition, the hydrophobic modified iron tailings powder can effectively absorb the residual phenol and formaldehyde in the concrete system after mixing, and can effectively reduce the environmental problems caused by the concrete raw materials without affecting the dispersion of the modified glass fiber and the formation of the "reinforcement body".

[0017] In summary, the iron tailings concrete obtained by the specific formula of the present application achieves the strength required for construction without affecting the fluidity of the concrete, and effectively improves the mechanical properties of the concrete.

[0018] Furthermore, the preparation method of the hydrophobically modified iron tailings powder comprises the following steps:

[0019] Sodium treatment: Take 2-2.5kg iron tailings powder, add 20-25L of 1mol / L NaCl solution, stir at 30-35℃ for 24-28h, remove the supernatant, wash with distilled water, and filter until no Cl is detected. - After drying, and activating at 105-110°C for 1-1.5h, sodium iron tailings powder is obtained;

[0020] Hydrophobic modification treatment: add 1-1.5kg sodium iron tailings powder to 10-15L deionized water to obtain a suspension, add 2-2.5L silane coupling agent KH550 dropwise while stirring at 40-45℃, then control the pH to 7-8 and continue stirring for 2-2.5h, remove the supernatant after standing, wash with distilled water, and filter until no Cl is detected. - After drying, and activating at 105-110° C. for 1-1.5 hours, a hydrophobically modified iron tailings powder base material is obtained;

[0021] Preparation of hydrophobically modified iron tailings powder: add 0.5-1 L of 35-40% formaldehyde aqueous solution to 1.5-2 kg of hydrophobically modified iron tailings powder base material while stirring, and stir for 20-30 minutes to obtain hydrophobically modified iron tailings powder.

[0022] By adopting the above technical scheme, the nanochemical treatment enables the hydrophobically modified iron tailings powder to obtain a stronger adsorption capacity, and the silane coupling agent KH550 can form a hydrophobic film on the surface of the iron tailings powder particles to improve the hydrophilicity of the iron tailings powder surface, thereby improving the fluidity of the concrete; and the hydrophobic film improves the roughness of the surface of the iron tailings powder particles, playing a lubricating role in the movement of the iron tailings sand particles.

[0023] After the hydrophobic modified iron tailings powder base material is mixed with the formaldehyde aqueous solution, the formaldehyde aqueous solution can be adsorbed by the hydrophobic modified iron tailings powder base material to obtain the hydrophobic modified iron tailings powder, so that the hydrophobic modified iron tailings powder can be combined with the modified glass fiber in the concrete system to form a "reinforcement body".

[0024] Furthermore, the preparation method of the modified glass fiber comprises the following steps:

[0025] Phenol is heated until it melts from crystals to liquid, and then mixed with chlorobutane in equal volumes and stirred to obtain a phenol-chlorobutane solution;

[0026] 1-2 parts by weight of calcium oxide are added to 40-45 parts of phenol-chlorobutane solution to obtain a mixture, and 15-20 parts by weight of glass fiber are added to 45-50 parts of the mixture and soaked for 15-20 minutes to obtain modified glass fiber.

[0027] By adopting the above technical scheme, the phenol-chlorobutane solution can effectively improve the dispersibility of the glass fiber, thereby further improving the crack resistance of the iron tailings concrete; the addition of calcium oxide can enable the modified glass fiber to combine with the hydrophobic modified iron tailings powder in the concrete system to form a "reinforcement body" under the residual heat of hydration heat.

[0028] Furthermore, the water reducing agent is a polycarboxylate water reducing agent.

[0029] Furthermore, the concrete also includes 3-4 parts by weight of sodium dodecylbenzene sulfonate.

[0030] Furthermore, the cement is ordinary Portland cement with a P·O 42.5, the slag powder is S95 grade granulated blast furnace slag powder, and the fly ash is grade II fly ash.

[0031] Furthermore, the fineness modulus of the river sand is 2.3-3.0, and the fineness modulus of the iron tailings sand is 1.6-2.2.

[0032] Furthermore, the fine stone is 5-10 mm continuously graded fine stone, and the crushed stone is 5-31.5 mm continuously graded crushed stone.

[0033] In a second aspect, the present application provides a method for preparing iron tailings concrete, using the following technical method:

[0034] A method for preparing iron tailings concrete comprises the following steps:

[0035] preparing a solid mixture: mixing cement, slag powder, fly ash, river sand, fine stone and crushed stone and stirring to obtain a solid mixture;

[0036] Preparing concrete slurry: adding the remaining raw materials except the hydrophobic modified iron tailings powder and the iron tailings sand into the solid mixture, and stirring to obtain concrete slurry;

[0037] Preparation of concrete: adding hydrophobic modified iron tailings powder and iron tailings sand into concrete slurry and stirring to obtain concrete.

[0038] By adopting the above technical scheme, concrete slurry is first prepared, and then hydrophobic modified iron tailings powder and iron tailings sand are added, which can reduce the possibility of poor concrete mixing due to water adsorbed on the surface of iron tailings sand; more importantly, the hydrophobic modified iron tailings powder is added last, which can avoid the situation where the formaldehyde adsorbed by the hydrophobic modified iron tailings powder particles evaporates too quickly and has no time to react without affecting the early dispersibility of the modified glass fiber, and can facilitate the hydrophobic modified iron tailings powder particles to effectively adsorb residual formaldehyde and phenol after the concrete system is naturally cooled, thereby reducing the environmental problems caused by the concrete raw materials.

[0039] Compared with the prior art, this application has the following technical effects:

[0040] 1. In the present application, iron tailings sand, hydrophobically modified iron tailings powder and river sand are used to form a mixed sand. Since the surface of the iron tailings sand and hydrophobically modified iron tailings powder particles are rough and the edges and corners are clear and sharp, after the concrete is solidified, the "pinning" and "biting" effects between the iron tailings sand particles, between the hydrophobically modified iron tailings powder particles, between the iron tailings sand particles and other solid particles in the concrete, and between the hydrophobically modified iron tailings powder particles and other solid particles in the concrete can improve the strength of the concrete.

[0041] However, because the surface of iron tailings sand particles is sharp, the friction between solid particles in the concrete system increases. The combination of hydrophobic modified iron tailings powder, iron tailings sand and river sand with smooth and round particle surfaces reduces the friction between particles in the concrete system and reduces the impact of iron tailings sand on the fluidity of concrete. By controlling the amount of iron tailings sand to between 20-30% of the total weight of the mixed sand, the content of particles with rough surfaces can be controlled to reduce the friction between rough iron tailings sand particles and between iron tailings sand particles and river sand particles, thereby reducing the impact of iron tailings sand on the fluidity of concrete.

[0042] In the present application, the sand ratio is controlled within an appropriate range by controlling the ratio of river sand, fine stone and crushed stone. The appropriate sand ratio allows the concrete to meet the strength requirements while improving the fluidity of the concrete. In the present application, iron tailings sand, river sand, fine stone and crushed stone of different particle sizes are used to form a good gradation between each other, so that the concrete obtains excellent density, thereby improving the strength of the concrete.

[0043] Iron tailings powder has a large specific surface area and strong water absorption capacity, which will have an adverse effect on the fluidity of concrete. In this application, the hydrophobically modified iron tailings powder surface after modification has a hydrophobic film, which reduces the impact of the iron tailings powder on the fluidity of concrete; and the hydrophobic film plays a lubricating role for the movement of the hydrophobically modified iron tailings powder particles, further improving the fluidity of the concrete. In addition, the modified glass fiber obtained by hydrophobic modification of phenol-chlorobutane solution can be better dispersed in the concrete system, effectively improving the crack resistance of the concrete.

[0044] More importantly, under the waste heat of concrete hydration, formaldehyde in the hydrophobic modified iron tailings powder can be evaporated, and the formaldehyde, silane coupling agent and phenol in the hydrophobic modified iron tailings powder and modified glass fiber can be cross-linked in the concrete system to form a "reinforcement body" in which a number of hydrophobic modified iron tailings powders are connected around the modified glass fiber; the "reinforcement body" has a linear modified glass fiber as the main frame and a number of granular hydrophobic modified iron tailings powders as "claws" to form a structure similar to a mace, so that the special structural characteristics of the "reinforcement body" enable it to have a "pinning" and "biting" effect with other solid particles in the concrete system, further improving the strength of the concrete; not only that, the micro-network structure formed by cross-linking of formaldehyde, silane coupling agent and phenol between the hydrophobic modified iron tailings powder and the modified glass fiber can further improve the mechanical properties of the concrete.

[0045] In addition, the hydrophobic modified iron tailings powder can effectively absorb the residual phenol and formaldehyde in the concrete system after mixing, and can effectively reduce the environmental problems caused by the concrete raw materials without affecting the dispersion of the modified glass fiber and the formation of the "reinforcement body".

[0046] In summary, the iron tailings concrete obtained by the specific formula of the present application achieves the strength required for construction without affecting the fluidity of the concrete, and effectively improves the mechanical properties of the concrete.

[0047] 2. Nanochemical treatment makes the hydrophobically modified iron tailings powder have stronger adsorption capacity, and the silane coupling agent KH550 can form a hydrophobic film on the surface of the iron tailings powder particles, which improves the fluidity of the concrete; and the hydrophobic film improves the roughness of the surface of the iron tailings powder particles and plays a lubricating role. After the hydrophobically modified iron tailings powder base material is mixed with the formaldehyde aqueous solution, the formaldehyde aqueous solution can be adsorbed by the hydrophobically modified iron tailings powder base material to obtain the hydrophobically modified iron tailings powder, so that the hydrophobically modified iron tailings powder can be combined with the modified glass fiber in the concrete system to form a "reinforcement body";

[0048] Phenol-chlorobutane solution can effectively improve the dispersibility of glass fiber, thereby further improving the crack resistance of iron tailings concrete; the addition of calcium oxide can enable the modified glass fiber to combine with the hydrophobic modified iron tailings powder in the concrete system to form a "reinforcement body" under the residual heat of hydration.

[0049] 3. In the present application, the polycarboxylate water-reducing agent introduces polycarboxylate molecules into the concrete, so that the cement particles are dispersed with each other, and the encapsulated water molecules are released, thereby greatly reducing the water consumption; and the polycarboxylate molecules will adsorb on the surface of the cement particles so that the surface of the cement particles has a negative charge, and the surfaces of the iron tailings and river sand are both negatively charged, so that the iron tailings, river sand, and cement particles with negative charges on the surface form an electrostatic repulsion effect, thereby improving the fluidity of the concrete;

[0050] The addition of sodium dodecylbenzene sulfonate as an air-entraining agent can further improve the fluidity of concrete; the river sand is selected from medium sand with a moderate fineness modulus, which is combined with iron tailings sand to improve the fluidity and strength of concrete; and the fine stone and crushed stone form a good gradation of step-by-step filling, which reduces the void ratio between concrete particles and increases the packing density, thereby enhancing the strength of concrete and achieving the purpose of saving cement at the same time.

[0051] 4. In the preparation method of the present application, the concrete slurry is prepared first, and then the hydrophobic modified iron tailings powder and iron tailings sand are added, which can reduce the possibility of poor concrete mixing due to water adsorbed on the surface of the iron tailings sand; more importantly, the hydrophobic modified iron tailings powder is added last, which can avoid the situation where the formaldehyde adsorbed by the hydrophobic modified iron tailings powder particles evaporates too quickly and has no time to react without affecting the early dispersibility of the modified glass fiber, and can facilitate the hydrophobic modified iron tailings powder particles to effectively adsorb residual formaldehyde and phenol after the concrete system is naturally cooled, thereby reducing the environmental problems caused by the concrete raw materials.

[0052] In summary, the iron tailings concrete of the present application can effectively solve the problem of low recycling rate of iron tailings, and prepare concrete with excellent strength and crack resistance. DETAILED DESCRIPTION

[0053] In the embodiments of the present application, the water reducing agent is a polycarboxylate water reducing agent; the cement is P·O 42.5 ordinary Portland cement; the slag powder is S95 grade granulated blast furnace slag powder; and the fly ash is grade II fly ash.

[0054] In the embodiment of the present application, the fineness modulus of the river sand is 2.3-3.0, the fineness modulus of the iron tailings sand is 1.6-2.2; the fine stone is 5-10mm continuously graded fine stone, and the crushed stone is 5-31.5mm continuously graded crushed stone; the fineness modulus of the hydrophobically modified iron tailings powder is 0.5-1.5.

[0055] Preparation example of hydrophobically modified iron tailings powder

[0056] Preparation Example 1

[0057] A method for preparing hydrophobically modified iron tailings powder comprises the following steps:

[0058] Sodium treatment: Take 2kg iron tailings powder, add 20L of 1mol / L NaCl solution, stir at 30℃ for 24h, remove the supernatant, wash with distilled water, and filter until no Cl is detected. - After drying, and activating at 105°C for 1h, sodium iron tailings powder was obtained;

[0059] Hydrophobic modification treatment: 1 kg sodium iron tailings powder was added to 10 L deionized water to obtain a suspension, and 2 L of silane coupling agent KH550 was added dropwise while stirring at 40 °C. Then the pH was controlled to 7-8 and stirring was continued for 2 h. After standing, the supernatant was removed and washed with distilled water and filtered until no Cl was detected. - After drying, and activating at 105°C for 1h, a hydrophobically modified iron tailings powder base material is obtained;

[0060] Preparation of hydrophobically modified iron tailings powder: 0.5 L of 35% formaldehyde aqueous solution was added to 1.5 kg of hydrophobically modified iron tailings powder base material while stirring, and the hydrophobically modified iron tailings powder was obtained after stirring for 20 minutes.

[0061] Preparation Example 2

[0062] A method for preparing hydrophobically modified iron tailings powder comprises the following steps:

[0063] Sodium treatment: Take 2.5kg iron tailings powder, add 25L of 1mol / L NaCl solution, stir at 35℃ for 28h, remove the supernatant, wash with distilled water, and filter until no Cl is detected. - After drying, and activating at 110°C for 1.5h, sodium iron tailings powder was obtained;

[0064] Hydrophobic modification treatment: 1.5 kg sodium iron tailings powder was added to 15 L deionized water to obtain a suspension, and 2.5 L silane coupling agent KH550 was added dropwise while stirring at 45 °C. Then the pH was controlled to 7-8 and stirring was continued for 2.5 h. After standing, the supernatant was removed and washed with distilled water and filtered until no Cl was detected. - After drying, and activating at 105°C for 1.5h, a hydrophobically modified iron tailings powder base material is obtained;

[0065] Preparation of hydrophobically modified iron tailings powder: 1 L of 40% formaldehyde aqueous solution was added to 2 kg of hydrophobically modified iron tailings powder base material while stirring, and the hydrophobically modified iron tailings powder was obtained after stirring for 30 minutes.

[0066] Preparation Example 3

[0067] A method for preparing hydrophobically modified iron tailings powder comprises the following steps:

[0068] Sodium treatment: Take 2.3kg iron tailings powder, add 23L of 1mol / L NaCl solution, stir at 30℃ for 26h, remove the supernatant, wash with distilled water, and filter until no Cl is detected. - After drying, and activating at 105°C for 1h, sodium iron tailings powder was obtained;

[0069] Hydrophobic modification treatment: 1.2 kg sodium iron tailings powder was added to 12 L deionized water to obtain a suspension, and 24 L of silane coupling agent KH550 was added dropwise while stirring at 40 °C. Then the pH was controlled to 7-8 and stirring was continued for 2 h. After standing, the supernatant was removed and washed with distilled water and filtered until no Cl was detected. - After drying, and activating at 105°C for 1h, a hydrophobically modified iron tailings powder base material is obtained;

[0070] Preparation of hydrophobically modified iron tailings powder: 0.7 L of 40% formaldehyde aqueous solution was added to 1.8 kg of hydrophobically modified iron tailings powder base material while stirring, and the hydrophobically modified iron tailings powder was obtained after stirring for 20 minutes.

[0071] Preparation example of modified glass fiber

[0072] Preparation Example 4

[0073] A method for preparing modified glass fiber comprises the following steps:

[0074] Phenol is heated until it melts from crystals to liquid, and then mixed with chlorobutane in equal volumes and stirred to obtain a phenol-chlorobutane solution;

[0075] 1 part by weight of calcium oxide is added to 40 parts by weight of phenol-chlorobutane solution to obtain a mixture, and 15 parts by weight of glass fiber is added to 45 parts of the mixture and soaked for 15 minutes to obtain modified glass fiber.

[0076] Preparation Example 5

[0077] A method for preparing modified glass fiber comprises the following steps:

[0078] Phenol is heated until it melts from crystals to liquid, and then mixed with chlorobutane in equal volumes and stirred to obtain a phenol-chlorobutane solution;

[0079] 2 parts by weight of calcium oxide are added to 45 parts of phenol-chlorobutane solution to obtain a mixture, and 20 parts by weight of glass fiber are added to 50 parts of the mixture and soaked for 20 minutes to obtain modified glass fiber.

[0080] Preparation Example 6

[0081] A method for preparing modified glass fiber comprises the following steps:

[0082] Phenol is heated until it melts from crystals to liquid, and then mixed with chlorobutane in equal volumes and stirred to obtain a phenol-chlorobutane solution;

[0083] 2 parts by weight of calcium oxide are added to 43 parts of phenol-chlorobutane solution to obtain a mixture, and 18 parts by weight of glass fiber are added to 48 parts of the mixture and soaked for 18 minutes to obtain modified glass fiber.

[0084] Comparative preparation example of modified glass fiber

[0085] Comparative Preparation Example 1

[0086] A method for preparing modified glass fiber comprises the following steps:

[0087] Phenol is heated until it melts from crystals to liquid, and then mixed with chlorobutane in equal volumes and stirred to obtain a phenol-chlorobutane solution;

[0088] 18 parts by weight of glass fiber were added into 48 parts of phenol-chlorobutane solution and soaked for 18 minutes to obtain modified glass fiber.

[0089] Comparative Preparation Example 2

[0090] A method for preparing modified glass fiber is carried out according to the method in Preparation Example 6, except that the mass of phenol-chlorobutane solution in the raw material is replaced by a silane coupling agent alcohol solution, and the silane coupling agent alcohol solution consists of 20% KH550, 72% ethanol and 8% water in volume percentage.

[0091] Comparative Preparation Example 3

[0092] A method for preparing modified glass fiber is carried out according to the method in Preparation Example 6, except that the mass of phenol-chlorobutane solution in the raw material is replaced by tetrachloroethane.

[0093] Example

[0094] Example 1

[0095] A method for preparing iron tailings concrete comprises the following steps:

[0096] preparing a solid mixture: mixing cement, slag powder, fly ash, river sand, fine stone and crushed stone and stirring to obtain a solid mixture;

[0097] Preparing concrete slurry: adding the remaining raw materials except the hydrophobic modified iron tailings powder and the iron tailings sand into the solid mixture, and stirring to obtain concrete slurry;

[0098] Preparing concrete: adding hydrophobic modified iron tailings powder and iron tailings sand into concrete slurry and stirring to obtain concrete;

[0099] Wherein, each component weight part is as follows:

[0100] 160 parts of cement, 70 parts of slag powder, 70 parts of fly ash, 630 parts of river sand, 140 parts of iron tailings sand, 130 parts of hydrophobic modified iron tailings powder, 200 parts of fine stone, 790 parts of crushed stone, 140 parts of water, 6 parts of water reducer, 70 parts of modified glass fiber; 4 parts of sodium dodecylbenzene sulfonate;

[0101] The hydrophobically modified iron tailings powder is prepared by the method in Preparation Example 1, and the modified glass fiber is obtained by the method in Preparation Example 4.

[0102] Example 2

[0103] A method for preparing iron tailings concrete comprises the following steps:

[0104] preparing a solid mixture: mixing cement, slag powder, fly ash, river sand, fine stone and crushed stone and stirring to obtain a solid mixture;

[0105] Preparing concrete slurry: adding the remaining raw materials except the hydrophobic modified iron tailings powder and the iron tailings sand into the solid mixture, and stirring to obtain concrete slurry;

[0106] Preparing concrete: adding hydrophobic modified iron tailings powder and iron tailings sand into concrete slurry and stirring to obtain concrete;

[0107] Wherein, each component weight part is as follows:

[0108] 180 parts of cement, 80 parts of slag powder, 80 parts of fly ash, 740 parts of river sand, 90 parts of iron tailings sand, 90 parts of hydrophobic modified iron tailings powder, 220 parts of fine stone, 820 parts of crushed stone, 165 parts of water, 10 parts of water reducing agent, 90 parts of modified glass fiber, 4 parts of sodium dodecylbenzene sulfonate;

[0109] The hydrophobically modified iron tailings powder is prepared by the method in Preparation Example 2, and the modified glass fiber is obtained by the method in Preparation Example 5.

[0110] Example 3

[0111] A method for preparing iron tailings concrete comprises the following steps:

[0112] preparing a solid mixture: mixing cement, slag powder, fly ash, river sand, fine stone and crushed stone and stirring to obtain a solid mixture;

[0113] Preparing concrete slurry: adding the remaining raw materials except the hydrophobic modified iron tailings powder and the iron tailings sand into the solid mixture, and stirring to obtain concrete slurry;

[0114] Preparing concrete: adding hydrophobic modified iron tailings powder and iron tailings sand into concrete slurry and stirring to obtain concrete;

[0115] Wherein, each component weight part is as follows:

[0116] 170 parts of cement, 75 parts of slag powder, 75 parts of fly ash, 670 parts of river sand, 120 parts of iron tailings sand, 120 parts of hydrophobic modified iron tailings powder, 210 parts of fine stone, 805 parts of crushed stone, 150 parts of water, 8 parts of water reducing agent, 80 parts of modified glass fiber, 3 parts of sodium dodecylbenzene sulfonate;

[0117] The hydrophobically modified iron tailings powder is prepared by the method in Preparation Example 3, and the modified glass fiber is obtained by the method in Preparation Example 6.

[0118] Comparative Example

[0119] Comparative Example 1

[0120] A method for preparing iron tailings concrete is carried out according to the method in Example 3, except that the raw material does not contain modified glass fiber, and the hydrophobic modified iron tailings powder in the raw material is replaced by iron tailings powder in an equal amount.

[0121] Comparative Example 2

[0122] A method for preparing iron tailings concrete is carried out according to the method in Example 3, except that an equal amount of raw material modified glass fiber is replaced by glass fiber, and an equal amount of hydrophobic modified iron tailings powder is replaced by iron tailings powder.

[0123] Comparative Example 3

[0124] A method for preparing iron tailings concrete is carried out according to the method in Example 3, except that the modified glass fiber in the raw material is replaced by glass fiber in equal amount.

[0125] Comparative Example 4

[0126] A method for preparing iron tailings concrete is carried out according to the method in Example 3, except that an equal amount of hydrophobic modified iron tailings powder in the raw material is replaced by iron tailings powder.

[0127] Comparative Example 5

[0128] A method for preparing iron tailings concrete is carried out according to the method in Example 3, except that the hydrophobically modified iron tailings powder in the raw material is replaced by an equal amount of the hydrophobically modified iron tailings powder base material in Preparation Example 3; specifically, the method for preparing the hydrophobically modified iron tailings powder base material comprises the following steps:

[0129] Sodium treatment: Take 2.3kg iron tailings powder, add 23L of 1mol / L NaCl solution, stir at 30℃ for 26h, remove the supernatant, wash with distilled water, filter until no Cl- is detected, dry, and activate at 105℃ for 1h to obtain sodium iron tailings powder;

[0130] Hydrophobic modification treatment: 1.2 kg of sodium iron tailings powder was added to 12 L of deionized water to obtain a suspension, and 24 L of silane coupling agent KH550 was added dropwise while stirring at 40 ° C. Then the pH was controlled to 7-8 and stirring was continued for 2 h. After standing, the upper clear liquid was removed, and washed and filtered with distilled water until Cl- was undetectable, then dried, and activated at 105 ° C for 1 h to obtain the hydrophobically modified iron tailings powder base material.

[0131] Comparative Example 6

[0132] A method for preparing iron tailings concrete is carried out according to the method in Example 3, except that the modified glass fiber in the raw material is prepared by the method in Comparative Preparation Example 1.

[0133] Comparative Example 7

[0134] A method for preparing iron tailings concrete is carried out according to the method in Example 3, except that the modified glass fiber in the raw material is prepared by the method in Comparative Preparation Example 2.

[0135] Comparative Example 8

[0136] A method for preparing iron tailings concrete is carried out according to the method in Example 3, except that the modified glass fiber in the raw material is prepared by the method in Comparative Preparation Example 3.

[0137] The comparison of the iron tailings powder and the glass fiber sources in each embodiment and each comparative example is shown in Table 1 below.

[0138] Table 1:

[0139]

[0140]

[0141] Performance Testing

[0142] The above embodiment is subjected to the following performance test, and the test results are shown in the table:

[0143] The compressive strength, slump and crack resistance of the concrete prepared in the above embodiments and comparative examples were measured by the experimental methods in GB / T 50081 and GB / T 50080. The test results are shown in Table 2. The slump data results in the table are rounded according to the requirement of 4.1.6 of GB / T 50080 that "the slump value of concrete mixture should be measured accurately to 1 mm, and the result should be rounded to 5 mm".

[0144] Table 2:

[0145]

[0146] Combining the data of Example 3 and Comparative Examples 1-4 in Table 2, it can be seen that the concrete in Example 3 is far superior to the concrete in Comparative Examples 1 and 2 in terms of strength, fluidity and crack resistance. The reason is that the concrete raw materials in Comparative Examples 1 and 2 do not contain hydrophobic modified iron tailings powder and modified glass fiber; and the reason why the concrete in Comparative Examples 3 and 4 is inferior to the concrete in Example 3 in terms of various properties is that the concrete raw materials in Comparative Examples 3 and 4 do not contain hydrophobic modified iron tailings powder and modified glass fiber at the same time. Although glass fiber can improve the crack resistance of concrete, the dispersibility of glass fiber in the system needs to be improved. Similarly, the iron tailings powder has a large specific surface area and a strong water absorption capacity, which will have an adverse effect on the fluidity of the concrete;

[0147] However, the raw materials in the concrete in Example 3 include the hydrophobically modified iron tailings powder and modified glass fiber disclosed in the present application, wherein the surface of the hydrophobically modified iron tailings powder has a hydrophobic film, and the hydrophobic film reduces the hydrophilicity of the surface of the hydrophobically modified iron tailings powder particles, thereby reducing the water absorption capacity of the hydrophobically modified iron tailings powder, allowing more water molecules to participate in the flow, so as to improve the fluidity of the concrete; and the hydrophobic film plays a lubricating role for the movement of the hydrophobically modified iron tailings powder particles, thereby improving the fluidity of the concrete. In addition, the modified glass fiber obtained by hydrophobic modification of the phenol-chlorobutane solution can be better dispersed in the concrete system, thereby further improving the crack resistance of the concrete.

[0148] More importantly, under the waste heat of concrete hydration, formaldehyde in the hydrophobically modified iron tailings powder can be evaporated, and the formaldehyde in the hydrophobically modified iron tailings powder, the silane coupling agent and the phenol in the modified glass fiber can be cross-linked in the concrete system to form a "reinforcement body" in which a number of hydrophobically modified iron tailings powders are connected around the modified glass fiber; the "reinforcement body" has a linear modified glass fiber as the main frame and a number of granular hydrophobically modified iron tailings powders as "claws" to form a structure similar to a mace, so that the special structural characteristics of the "reinforcement body" enable it to have a "pinning" and "biting" effect with other solid particles in the concrete system, further improving the strength of the concrete; not only that, the microscopic network structure formed by cross-linking of formaldehyde, silane coupling agent and phenol between the hydrophobically modified iron tailings powder and the modified glass fiber can further improve the mechanical properties of the concrete;

[0149] Moreover, the hydrophobically modified iron tailings powder can effectively absorb the residual phenol and formaldehyde in the concrete system after mixing, and can effectively reduce the environmental problems caused by the concrete raw materials without affecting the dispersibility of the modified glass fiber and the formation of the "reinforced body". It can also be explained that the iron tailings concrete of the present application can effectively solve the problem of low recycling rate of iron tailings, and prepare concrete with excellent strength and crack resistance.

[0150] Combining Example 3 and Comparative Example 5, Comparative Example 6 and the data of the three in Table 2, it can be seen that: compared with Example 3, the concrete strength and crack resistance of Comparative Example 5 and Comparative Example 6 are also inferior to those of the concrete in Example 3. This is because the hydrophobic modified iron tailings powder base material selected in Comparative Example 5 lacks formaldehyde, and the modified glass fiber in Comparative Example 6 lacks calcium oxide during preparation. Therefore, the hydrophobic modified iron tailings powder and modified glass fiber in the concrete system of the two are difficult to form a "reinforced body" that can effectively improve the strength and crack resistance of concrete.

[0151] Combining Example 3 and Comparative Examples 7-8 and their data in Table 2, it can be found that the difference between Comparative Examples 7-8 and Example 3 is that different hydrophobic modifiers are used when preparing the modified glass fibers. In Example 3, the hydrophobic modifier is the phenol-chlorobutane solution disclosed in the present application, so that the dispersibility of the modified glass fibers can be significantly improved, further reducing the possibility of aggregation of the modified glass fibers and affecting the number of "reinforcements" formed. The ability to form more "reinforcements" can further improve the strength and crack resistance of the concrete.

[0152] It can be found in Tables 1 and 2 that the slump values ​​of Comparative Examples 6, Comparative Examples 7, and Comparative Examples 8 are consistent after rounding, indicating that the difference in slump between the three is less than 5 mm, and the results are relatively close but better than Comparative Example 3. This may be due to the fact that the glass fibers in the three raw materials are all modified and can be better dispersed in the concrete system than ordinary glass fibers, so that the performance of concrete is improved, but the effect of the glass fiber itself and the modification of the glass fiber on the slump of concrete is not as great as that of the iron tailings powder, so the slump results of the three are improved compared with Comparative Example 3, but the gap between Comparative Examples 6, 7, and 8 is not large. On this basis, Comparative Examples 6, 7, and 8 are compared with Example 3, which can further prove that the preparation method of the modified glass fiber selected in Example 3 can form a "reinforced body" that can effectively improve the strength and crack resistance of concrete by hydrophobically modified iron tailings powder and modified glass fiber in the system.

[0153] The specific embodiments in this application are merely explanations of this application and are not limitations of this application. After reading this specification, those skilled in the art may make modifications to this embodiment without any creative contribution as needed, but as long as they are within the scope of the claims of this application, they are protected by the patent law.

Claims

1. An iron tailings concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 160-180 parts of cement, 70-80 parts of slag powder, 70-80 parts of fly ash, 630-740 parts of river sand, 90-140 parts of iron tailings sand, 90-130 parts of hydrophobic modified iron tailings powder, 200-220 parts of fine stone, 790-820 parts of crushed stone, 140-165 parts of water, 6-10 parts of water reducer, 70-90 parts of modified glass fiber; The hydrophobically modified iron tailings powder is obtained by modifying the iron tailings powder with a silane coupling agent KH550 and a formaldehyde aqueous solution, and the hydrophobically modified iron tailings powder has a fineness modulus of 0.5-1.5; The modified glass fiber is obtained by modifying the glass fiber with a phenol-chlorobutane solution and calcium oxide.

2. The iron tailings concrete according to claim 1, characterized in that: The preparation method of the hydrophobically modified iron tailings powder comprises the following steps: Sodium treatment: Take 2-2.5kg iron tailings powder, add 20-25L of 1mol / L NaCl solution, stir at 30-35℃ for 24-28h, remove the supernatant, wash with distilled water, and filter until no Cl is detected. - After drying, and activating at 105-110°C for 1-1.5h, sodium iron tailings powder is obtained; Hydrophobic modification treatment: 1-1.5 kg sodium iron tailings powder is added to 10-15 L deionized water to obtain a suspension, and 2-2.5 L silane coupling agent KH550 is added dropwise while stirring at 40-45 ° C, and then the pH is controlled to 7-8 and continued to stir for 2-2.5 hours. After standing, the upper clear liquid is removed, and washed and filtered with distilled water until Cl- is undetectable, and then dried, and activated at 105-110 ° C for 1-1.5 hours to obtain a hydrophobically modified iron tailings powder base material; Preparation of hydrophobically modified iron tailings powder: add 0.5-1 L of 35-40% formaldehyde aqueous solution to 1.5-2 kg of hydrophobically modified iron tailings powder base material while stirring, and stir for 20-30 minutes to obtain hydrophobically modified iron tailings powder.

3. The iron tailings concrete according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises the following steps: Phenol is heated until it melts from crystals to liquid, and then mixed with chlorobutane in equal volumes and stirred to obtain a phenol-chlorobutane solution; 1-2 parts by weight of calcium oxide are added to 40-45 parts of phenol-chlorobutane solution to obtain a mixture, and 15-20 parts by weight of glass fiber are added to 45-50 parts of the mixture and soaked for 15-20 minutes to obtain modified glass fiber.

4. The iron tailings concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylate water reducing agent.

5. The iron tailings concrete according to claim 1, characterized in that: The concrete also includes 3-4 parts by weight of sodium dodecylbenzene sulfonate.

6. The iron tailings concrete according to claim 1, characterized in that: The cement is P·O 42.5 ordinary Portland cement, the slag powder is S95 grade granulated blast furnace slag powder, and the fly ash is grade II fly ash.

7. The iron tailings concrete according to claim 1, characterized in that: The fineness modulus of the river sand is 2.3-3.0, and the fineness modulus of the iron tailings sand is 1.6-2.

2.

8. The iron tailings concrete according to claim 1, characterized in that: The fine stone is 5-10 mm continuously graded fine stone, and the crushed stone is 5-31.5 mm continuously graded crushed stone.

9. A method for preparing iron tailings concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: preparing a solid mixture: mixing cement, slag powder, fly ash, river sand, fine stone and crushed stone and stirring to obtain a solid mixture; Preparing concrete slurry: adding the remaining raw materials except the hydrophobic modified iron tailings powder and the iron tailings sand into the solid mixture, and stirring to obtain concrete slurry; Preparation of concrete: adding hydrophobic modified iron tailings powder and iron tailings sand into concrete slurry and stirring to obtain concrete.